Sebaran Fraksi dan Jenis Sedimen Dasar (Bed-Load) di Sungai Pawan Kecamatan Delta Pawan Kabupaten Ketapang - Nursiani, Tuti; Putra, Yoga Satria; Muhardi, Muhardi (Journal of Marine and Aquatic Sciences, 2020)
Pawan River is the longest river in Ketapang Regency which has been silting due to sedimentation in the riverbed. A study on sediment transport in areas with potential siltation needs to be conducted. This purpose of tis study was to identify the distribution and types of bed-load in the area by using the hydrometer method. This study was conducted at five locations, and each location was conducted three measurement points. The results showed that the types of bed-load were clay, silty clay, clay loam, loam, silt loam, sandy loam, loamy sand. While, the distribution of sediment fraction were sand (0.05 - 2 mm) of 32.07%, silt (0.002-0.05 mm) of 42.60%, and clay (<0.002 mm) of 24.87%.